Bank Performance Before And During Crisis Due To Covid-19 - Yuga Casandri; Rosyadi Rosyadi; Jumhur Jumhur (Jurnal Ekonomi-Qu, 2022)
We examine the differences in banking performance of CAMEL ratio of government-owned conventional banks in Indonesia, before and during the crisis due to Covid-19 (Q1-Q3 2019 and Q1-Q3 2020). Then we examine the determinants of bank performance itself during those period. Using paired sample t-test, we found that there was no significant difference of CAMEL ratio, before and during crisis. Using panel regression, partially, we found only OEOI, Interest Rates and Economic Crisis have significant effect on bank performance that reflected by ROA & ROE. Simultaneously, all independent variables have significant effect on banking performance that reflected by ROA and ROE.